Detection of bacteriuria by automated electrical impedance monitoring in a clinical microbiology laboratory. - Throm, R (1977)
An apparatus capable of rapidly detecting changes in electrical impedance was utilized for the continuous monitoring of bacterial growth in routine urine specimens in a clinical laboratory. In a trial study, 200 clinical specimens analyzed by the electrical impedance method resulted in an average detection time of 2.5 h for 41 clinically significant specimens, whereas conventional methods for bacterial isolation required overnight culture. Those specimens positive by the electrical impedance monitoring but negative by conventional bacteriological methods accounted for less than 2% of the total number of positive specimens, whereas electrical impedance-negative but conventional culture-positive specimens accounted for ca. 4%. Electrical impedance apparatus in clinical microbiology laboratories could provide rapid screening of clinical urine specimens as well as accurate detection of bacterial growth.